Cloning, purification, crystallization and preliminary X-ray studies of human α(1)-microglobulin - Zhang, Yangli (International Union of Crystallography, 2012)
α(1)-Microglobulin (α(1)m) is one of the phylogenetically most widespread lipocalins and is distributed in various organs and tissues, including liver, heart, eye, kidney, brain, lung, pancreas and skeletal muscle. α(1)m has been found to exert multifarious functions, including interacting with IgA, albumin and prothrombin, binding strongly to haem and exhibiting reductase activity. Nevertheless, little structural information is available regarding these functions of α(1)m. Since determination of three-dimensional structure is a powerful means of functional characterization, X-ray crystallography was used to accomplish this task. Here, the expression, purification, crystallization and preliminary crystallographic analysis of human α(1)m are reported. The crystal belonged to space group P4(3), with unit-cell parameters a = b = 36.45, c = 112.68 Å, and diffracted to a resolution of 2.0 Å. The crystals are most likely to contain one molecule in the asymmetric unit, with a V (M) value of 1.63 Å(3) Da(−1).